Gold-Catalysed Cycloisomerisation of Ynamides To Access 2,2-Disubstituted Tetrahydrothiophene Motifs - Kaur, Parmjit Heer; Davies, Paul W. (Synlett, 2021)
Ynamides bearing a tethered allyl sulfoxide undergo a gold-catalysed cycloisomerisation to afford tetrahydrothiophene-2-carboxamides and their benzo-fused analogues. The reactions are initiated by a formal 7-endo-dig cyclisation and accommodate a range of different substituents. The use of N-allyl ynamides provided a route into novel spirocyclic ε-lactam structures.
Keywords: gold; ynamides; isomerization; ylides; regioselectivity; thiophenecarboxamides